Bacillus amyloliquefaciens SC06 alleviates the obesity of ob/ob mice and improves their intestinal microbiota and bile acid metabolism. Issue 9 (26th April 2022) - Zeng, Zhonghua; Zhou, Yuanhao; Xu, Yibin; Wang, Song; Wang, Baikui; Zeng, Zihan; Wang, Qi; Ye, Xiaolin; Jin, Lu; Yue, Min; Tang, Li; Zou, Peng; et al.
Abstract : Bacillus amyloliquefaciens SC06 can ameliorate obesity in male ob/ob mice by reshaping the intestinal microbial composition, changing metabolites, with deep correlation between phenotypes, and regulating bile acid metabolism via the FXR signaling pathway. Abstract : Dietary interventions with probiotics have been widely reported to be effective in regulating obesity, and the intestinal microbiota is considered to be an important environmental factor. However, few reports focus on the interactions of microbiota–metabolites–phenotypic variables in ob/ob mice, and they have not been characterized in great detail. In this study, we investigated the effects of Bacillus amyloliquefaciens SC06 on obesity, the intestinal microbiota and the bile acid metabolism of ob/ob mice using biochemical testing, histochemical staining, high-throughput sequencing of the 16S rRNA gene, LC-MS/MS analysis and qRT-PCR. The results showed that SC06 ameliorated the fat mass percentage, hepatic steatosis and liver lipid metabolism disorders and reshaped the gut microbiota and metabolites in male ob/ob mice, specifically deceasing f_S24-7, p_TM7, s_Alistipes massiliensis, f_Rikenellaceae, f_Prevotellaceae, f_Lactobacillaceae, g_Alistipes, g_Flexispira, g_Lactobacillus, g_Odoribacter, g_AF12 and g_Prevotella and increasing f_Bacteroidaceae, g_Bacteroides and f_Desulfovibrionaceae . Meanwhile, SC06 treatment groups had lower ibuprofen and higher glycodeoxycholic acid and 7-dehydrocholesterol. Correlation analysis further clarified the relationships between compositional changes in the microbiota and alterations in the metabolites and phenotypes of ob/ob mice. Moreover, SC06 downregulated bile acid synthesis, export and re-absorption in the liver and increased ileum re-absorption into the blood in ob/ob mice, which may be mediated by the FXR-SHP/FGF15 signaling pathway. These results suggest that Bacillus amyloliquefaciens SC06 can ameliorate obesity in male ob/ob mice by reshaping the intestinal microbial composition, changing metabolites and regulating bile acid metabolism via the FXR signaling pathway.